Increased choroidal mast cells and their degranulation in age-related macular degeneration - Bhutto, Imran A (Br J Ophthalmol, 2016)
BACKGROUND/AIMS: Inflammation has been implicated in age-related macular degeneration (AMD). This study investigates the association of mast cells (MCs), a resident choroidal inflammatory cell, with pathological changes in AMD. METHODS: Human donor eyes included aged controls (n=10), clinically diagnosed with early AMD (n=8), geographic atrophy (GA, n=4), and exudative AMD (n=11). The choroids were excised and incubated alkaline phosphatase (APase; blood vessels) and nonspecific esterase activities (MCs). Degranulated (DG) and nondegranulated (NDG) MCs in four areas of posterior choroid (nasal, nonmacular, paramacular, and submacular) were counted in flat mounts (4∼6 fields/area). Choroids were subsequently embedded in JB-4 and sectioned for histological analyses. RESULTS: The number of MCs was significantly increased in all choroidal areas in early AMD (p=0.0006) and in paramacular area in exudative AMD (139.44±55.3 cells/mm(2); p=0.0091) and GA (199.08±82.0 cells/mm(2); p=0.0019) compared to the aged controls. DG MCs was also increased in paramacular (p=0.001) and submacula choroid (p=0.02) in all forms of AMD. Areas with the greatest numbers of DG MC had loss of choriocapillaris (CC). Sections revealed that the MCs were widely distributed in Sattler's and Haller's layer in the choroidal stroma in aged controls, whereas MCs were frequently found in close proximity to CC in GA and exudative AMD and in choroidal neovascularization (CNV). CONCLUSION: Increased MC numbers and degranulation were observed in all AMD choroids. These results suggest that MC degranulation may contribute to the pathogenesis of AMD: death of CC and RPE and CNV formation. The proteolytic enzymes released from MC granules may result in thinning of AMD choroid.